Influence of multi-scale dynamics on the vertical nitrate distribution around the Kuroshio Extension: An investigation based on BGC-Argo and satellite data. (April 2021) - Wang, Tao; Chai, Fei; Xing, Xiaogang; Ning, Jue; Jiang, Wensheng; Riser, Stephen C.
Highlights: Subsurface elevated nitrate was observed inside a cyclonic eddy. Elevated nitrate and CHL were observed along the edge of an anti-cyclonic eddy. Submesoscale process likely played significant roles in elevating nitrate and CHL. Abstract: The vertical delivery of nutrients from deep water into the euphotic zone is one of the major limitations for the ocean primary productivity. In this study, the influence of multi-scale dynamics on the nitrate distribution observed by two BGC-Argo floats around the Kuroshio Extension is investigated. Vertical fluctuations of iso-nitrate surfaces and isopycnals were found to be correlated to the variation of absolute dynamic topography. In the subtropical Northwestern Pacific Ocean, subsurface nitrate concentration was found to be elevated inside a cyclonic mesoscale eddy during summer, while little nitrate was supplied into the surface layer, which was possibly due to the inhibition of seasonal thermocline. On the northern edge of the Kuroshio Extension, elevated euphotic-layer nitrate and surface chlorophyll concentrations were observed along the periphery of an anti-cyclonic eddy. In addition to horizontal advection, upwelling induced by the submesoscale dynamics is suggested to likely play an important role in the enhancements of nitrate and chlorophyll concentrations. The enhanced vertical delivery of nutrients from depth due to submesoscale dynamics has been hypothesized as a significant source for some satellite-observed events of high surface chlorophyll concentration, but direct evidence from in-situ observations is lacking. In this study, the synchronous occurrence of elevated nitrate and chlorophyll concentrations along the periphery of an anti-cyclonic eddy provides an evidence to support this hypothesis to some extent.